1999
DOI: 10.1097/00000542-199909000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microembolism Diagnosed by Transcranial Doppler during Total Knee Arthroplasty 

Abstract: Cerebral microembolism occurs frequently during tourniquet release, even in the absence of a patient foramen ovale. This passage most likely occurs through the pulmonary capillaries or the opening of recruitable pulmonary vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 27 publications
0
49
0
7
Order By: Relevance
“…This appears to be assessed as part of routine follow-up, though 1 study specifically undertook neurologic examinations. 20 Six studies measured cognitive function, and 1 study measured quality of life postoperatively as a proxy for cognition. 13 No study found an association between neurologic or cognitive change and embolic count.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to be assessed as part of routine follow-up, though 1 study specifically undertook neurologic examinations. 20 Six studies measured cognitive function, and 1 study measured quality of life postoperatively as a proxy for cognition. 13 No study found an association between neurologic or cognitive change and embolic count.…”
Section: Resultsmentioning
confidence: 99%
“…Some reports have found numerous disadvantages associated with tourniquet use, including reduced early knee flexion [11,14,60,62,65], increased perioperative pain [11,14,27,56,57], increased postoperative limb swelling [11,21,47], more frequent wound complications [9,12,40,41], an increase in cardiac and cerebral microemboli [16,20,[42][43][44]55], an increased incidence of deep venous thrombosis [8,57,65], an increased risk of arterial thrombosis in subjects with preoperative vascular disease [22,26,48], a risk of peripheral nerve injury [29,39], and skin irritation from tourniquet application [13].…”
Section: Introductionmentioning
confidence: 99%
“…The former presumes that fractures of marrow containing bone have the highest incidence of FES due to disrupted venules in the marrow which are tethered open by osteous attachments that allows easy entry of marrow contents into the circulation [7]. From there on, it can enter the arterial circulation via a patent for men ovale (PFO) causing increases in pulmonary artery and right heart pressures or by micro embolism via the lung demonstrated even in the absence of a PFO; the latter could explain the neurologic disease and petechiae associated with FES [8,9]. The bio chemical theory or mechanism explains that destabilization of a plasma chylomicronemulsion lead stocoalescence off at stores [10,11].…”
Section: Discussionmentioning
confidence: 99%